Engagement Académico y Resiliencia en estudiantes Universitarios de Bolivia y Ecuador - Soria Coba Mary Andrea (2025)
This study analyzes the relationship between Academic Engagement and Resilience in university students in the last semesters of the Psychopedagogy degree, considering the context of two Latin American educational institutions: the National University of Chimborazo in Ecuador and the Domingo Savio Private University in Bolivia. The research is based on the premise that active commitment to learning and the ability to overcome adversity are crucial factors in the formative process and student well-being. Methodologically, this research has a quantitative approach, a non-experimental design, by correlational scope, by basic objective, by field location, by transversal time; the population were university students in the last semesters of the Psychopedagogy degree from both universities. The sample was selected in a non-probabilistic way and for data processing, the psychometric technique was used with the instruments of the UWES-S17 and ER-14 scales, the level of Academic Engagement and Resilience were evaluated. The results offer a comparative view of how these variables interact in diverse educational contexts. They conclude that no significant correlation was found at the National University of Chimborazo, while a moderately significant positive correlation was found at the Domingo Savio Private University. This provides a basis for designing strategies to enhance academic performance, resilience, and emotional well-being in university students.